2019
DOI: 10.1155/2019/2634738
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Presentation of Insert Dislocation and MCL Rupture in Unicompartmental Knee Replacement with 2 Years Postoperative Results: Does It Functional?

Abstract: According to our knowledge, there is no prior article that reports functional results of medial collateral ligament (MCL) primary repair and insert change after MCL rupture and mobile-bearing dislocation as a late complication of unicompartmental knee replacement (UKR). Firstly, 63-year-old woman was treated with UKR due to anteromedial knee osteoarthritis of the right knee joint. 1 year after UKR surgery, she suffered from MCL rupture and mobile-bearing dislocation because of falls while getting on a public b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Inicialmente, las prótesis se implantaban a pacientes mayores de 60 años, que tienen un nivel de actividad relativamente sedentario [7,8]. Sin embargo, en los últimos años, se están implantando prótesis a pacientes más jóvenes y activos.…”
Section: Discussionunclassified
“…Inicialmente, las prótesis se implantaban a pacientes mayores de 60 años, que tienen un nivel de actividad relativamente sedentario [7,8]. Sin embargo, en los últimos años, se están implantando prótesis a pacientes más jóvenes y activos.…”
Section: Discussionunclassified
“…This could be explained by determining exactly how bearing dislocation occurs. We explored related research [ 5 , 23 25 ] of bearing dislocation mechanisms and identified five possible mechanisms: (1) bearing rotation due to malposition of the metallic component, (2) an imbalanced flexion–extension gap, (3) cam impingement, (4) medial collateral ligament (MCL) dysfunction or injury, and (5) an improper bearing size. In fact, these dislocation mechanisms may not exist alone, and the collaboration of multiple mechanisms may underlie the main process of bearing dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by determining exactly how bearing dislocation occurs. We explored related research [5,[23][24][25] In fact, these dislocation mechanisms may not exist alone, and the collaboration of multiple mechanisms may underlie the main process of bearing dislocation. The Oxford UKA system is anatomically designed to match the spherical design of the femoral component.…”
Section: Discussionmentioning
confidence: 99%